Risk assessment for sewerage asset using spatial indicator - Nurshuhada Abd. Sukor, 1994-, author; Zakri Tarmidi, supervisor; Fakulti Geoinformasi dan Harta Tanah (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2017